The Influence of Service Quality and Company Image on Customer Satisfaction: Study Of One of The Companies Operating in The Banking Sector in Garut - Jannah, Dara Fitria; Larashati, Irena; Dwiyanisa, Ashila; Megawati, Imelda (Center of Research, STIE Pasundan, Bandung, Indonesia., 2024)
Banking, as a financial organization primarily engaged in the collection and redistribution of public funds, must establish a robust banking system. Consequently, it is necessary to regulate and supervise banking operations to ensure the adoption of sound banking practices. Since the implementation of the OJK Law on 22 November 2011, the oversight of financial services institutions in Indonesia has shifted from multiple institutions to a single institution, the OJK. Previously, banking supervision was conducted by Bank Indonesia, while Bapepam handled the supervision of capital markets and other financial institutions. The objective of this study is to ascertain customer happiness, which is influenced by the quality of service and the organization's image. This research employs the descriptive and verification analytic approach, focusing on the 92 respondents who are customers of Bank Negara Indonesia. The processing and research are categorized into two distinct types: secondary data from the company and primary data from the questionnaire responses; in-depth analysis is also done, which seeks to provide a comprehensive understanding of how service quality and corporate image impact customer happiness. According to the research findings, Service Quality is pretty good, with an average rating of 3.23. Company Image is also considered quite good, with an average rating of 3.18. Similarly, Customer Satisfaction falls into the pretty good area. Its mean value is 3.10. Service Quality (X1) significantly influences Customer Satisfaction (Y) with a total influence of 0.334. Similarly, Company Image (X2) also significantly influences Customer Satisfaction (Y) with a total influence of 0.484. When both Service Quality (X1) and Company Image (X2) are considered together, they have a combined influence on Customer Satisfaction (Y) with a determination (R2) of 0.818 or 81.8%. The remaining 18.2% of the influence on Customer Satisfaction (Y) is attributed to other variables that were not examined. The research findings confirm a strong correlation between Service Quality and Company Image Customer Satisfaction in a banking company in Garut.